3‐Aryl Coumarin Derivatives Bearing Aminoalkoxy Moiety as Multi‐Target‐Directed Ligands against Alzheimer's Disease. Issue 5 (8th April 2019) - Abdshahzadeh, Helia; Golshani, Mostafa; Nadri, Hamid; Saberi Kia, Iraj; Abdolahi, Zahra; Forootanfar, Hamid; Ameri, Alieh; Tüylü Küçükkılınç, Tuba; Ayazgok, Beyza; Jalili‐Baleh, Leili; Sadat Ebrahimi, Seyed Esmaeil; Moghimi, Setareh; et al.
Abstract: Two series of novel coumarin derivatives, substituted at 3 and 7 positions with aminoalkoxy groups, are synthesized, characterized, and screened. The effect of amine substituents and the length of cross‐linker are investigated in acetyl‐ and butyrylcholinesterase (AChE and BuChE) inhibition. Target compounds show moderate to potent inhibitory activities against AChE and BuChE. 3‐(3, 4‐Dichlorophenyl)‐7‐[4‐(diethylamino)butoxy]‐2 H ‐chromen‐2‐one (4y ) is identified as the most potent compound against AChE (IC50 =0.27 μm ). Kinetic and molecular modeling studies affirmed that compound 4y works in a mixed‐type way and interacts simultaneously with the catalytic active site (CAS) and peripheral anionic site (PAS) of AChE. In addition, compound 4y blocks β‐amyloid (Aβ) self‐aggregation with a ratio of 44.11 % at 100 μm and significantly protects PC12 cells from H2 O2 ‐damage in a dose‐dependent manner. Abstract :